INTERACTIVITY AND CUSTOMER ENGAGEMENT: ITS INFLUENCE ON PURCHASING DECISIONS ON SHOPEE LIVE "SURVEY ON EIGER ADVENTURE CONSUMERS IN INDONESIA" - Dharmawan, Reggy; Sugiono, Arif; Nugeraha, Prasetya (JURNAL ILMU MANAJEMEN, 2024)
Advances in information technology have enabled e-commerce platforms such as Shopee to develop new ways to facilitate online shopping, namely by presenting a live streaming feature. This feature is used as a promotional medium and to present products as well as to build relationships with customers. The convenience offered by live e-commerce shopping has made many consumers switch from conventional online shopping methods. This research aims to measure the influence of interactivity and customer engagement on consumer purchasing decisions for Eiger Adventure via Shopee Live. This research is included in the explanatory research category using a quantitative approach. The sampling method in this research used nonprobability sampling with purposive sampling technique. The sample consisted of 385 respondents who had purchased Eiger Adventure products via Shopee Live. The data collected from the questionnaire is then processed and analyzed which includes validity tests, reliability tests, classical assumption tests and multiple linear regression tests. The results of this research show that interactivity and customer engagement each have a positive and significant effect on purchasing decisions. Simultaneously, interactivity and customer engagement also have a positive and significant effect on purchasing decisions.